Inhibiting Integrin αvβ5 Reduces Ischemia–Reperfusion Injury in an Orthotopic Lung Transplant Model in Mice. Issue 4 (22nd January 2016) - Mallavia, B.; Liu, F.; Sheppard, D.; Looney, M. R.
Abstract : Primary graft dysfunction after lung transplantation is the leading cause of morbidity and mortality in the immediate posttransplant period and is characterized by endothelial and epithelial barrier disruption and the leakage of protein‐rich edema fluid. Integrins are cell surface receptors that have an important role in maintenance of the cell barrier, and inhibition of integrins, such as αvβ5, can diminish alveolar flooding in lung injury models. We hypothesized that inhibition of αvβ5 during donor lung cold ischemia would reduce endothelial permeability during reperfusion. Using an orthotopic single lung transplantation model with and without cold ischemia, donor lungs were perfused with αvβ5‐blocking antibody (ALULA) or control antibody at the time of collection, followed by transplantation, 8 h of reperfusion, and the measurement of lung injury parameters. Prolonged cold ischemia (18 h) produced increases in extravascular lung water, protein permeability, and neutrophilic alveolitis and decreased oxygenation compared with lungs without cold ischemia. Perfusion of lungs with αvβ5 antibody versus control antibody protected donor lungs from injury and significantly improved oxygenation. In summary, αvβ5 integrin blockade protects from the development of ischemia–reperfusion lung injury and is a promising approach to preventing primary graft dysfunction in human lung transplant procedures. Abstract : In this study, the authors demonstrate that treatment with a blocking antibody against integrin 〈v ® 5 reduces primary graft dysfunction after lung transplantation in mice.